IDENTIFICATION OF BALINESE ORNAMENTS AT THE ENTRANCE OF THE AL-HIKMAH MOSQUE, DENPASAR - Putu Ari Darmastuti (Journal of Aesthetics, Design, and Art Management, 2021)
Purpose : Religious buildings generally follow the form, function and decoration of the area oforigin of the religion. Islam in Bali began to spread during the reign of King Dalem Waturenggongwho was centered in Klungkung Regency in the fourteenth century. Since the first time Islamentered and developed in Bali, until now several mosque buildings have experienced adaptation andacculturation with Balinese culture. Adaptation and acculturation are more dominantly affected inreligious buildings because there is no separate style of how the appearance and embodiment of amosque building. In Denpasar City, there are not many mosque buildings that are affected byBalinese culture.Research methods : The research method used is interpretive qualitative. Etymologically,qualitative, comes from quality which means value.Findings : Along with the development and spread of Islam in the archipelago, the architecture ofthe mosque also experienced developments that adapted to each regional culture.Implications : Through architecture, regional culture and religion merge into a strong identity. Inthe architecture there are several elements, one of which is an aesthetic element in the form of anornamental. In this case, the identification of ornaments at Masjid Al-Hikmah entrance is classifiedbased on the four types of ornaments mentioned in the Nusantara Ornaments book, namely:geometric motifs, human motifs, animal motifs, motifs, plants, motifs of natural objects.